Computation of Bandwidth Distribution for Video Servers - Rodrigues, Carlo Kleber da S.; Leão, Rosa Maria Meri (Proceedings of the Workshop on Performance of Computer and Communication Systems (WPerformance), 2004)
Several bandwidth sharing techniques have been proposed to provide more scalability to video servers. The patching technique has several advantages such as simplicity of implementation and efficiency in terms of average bandwidth savings. However, the average bandwidth does not always provide an accurate estimation in order to guarantee a given level of QoS to the clients. We thus propose an analytical model to calculate the distribution of the number of streams generated by the patching technique, that is, the bandwidth distribution. Moreover, we investigate the use of this distribution to allocate the bandwidth in order to provide a given level of QoS to the clients, to estimate the QoS when some system parameter values change, and to dimension the server.